Development and application of an LC-MS/MS method for quantification of fosmidomycin in human and rat plasma - Pfaffendorf, Christoph; Sackmann, Keanu D.; Mischlinger, Johannes; Dejon-Agobé, Jean Claude; Maïga-Ascofaré, Oumou; Ahenkan, Ebenezer; Adegnika, Ayôla Akim; Ramharter, Michael; Uhl, Philipp; Fricker, Gert; Wicha, Sebastian Georg (Malaria journal, 2025)
Malaria still poses a significant burden on global health, with millions of cases reported annually and rising resistance to current treatments, emphasizing the need for new therapeutic strategies. Fosmidomycin, initially recognized for its antibacterial properties, has emerged as a promising candidate in the fight against malaria.
Gesehen am 11.12.2025